"Da infância longínqua à ancianidade presente": tempos e vivências de Cora Coralina (séculos XIX - XX) - Oliveira, Elis Regina da Silva (2023)
This thesis is linked to the State, Policies and History of Education research line of the Postgraduate Program in Education at the Federal University of Goiás. Sedimented in this field, the guiding threads intertwine literature, history and education with the purpose of bringing to light experiences socio-historical aspects of formal and informal education in the state of Goiás at the end of the 19th century, as well as female performance in the limitless society of Goiás in the 20th century. For this exercise of crossing knowledge and perspectives, we took the set of poetic works by Cora Coralina (1889-1985), published during her lifetime, as an object of study revealed from a historical time that unites ‘distant childhood with present age’. Cora Coralina, in her literary writing, demystified the romantic vision of childhood and portrayed a panorama of all the lives she carried within herself. In this mosaic of experiences, we find several images of the ways of instructing and educating children, youth and other stages of life. In view of this, we record the poet's writing state as a 'place of memory' and memories of an adult, distant in time, about her childhood and other times. With her reminiscences, Cora Coralina presents us with different ways of thinking about history, of reviving memory, of reconstituting space. This means that through the pages of the literary text a certain historical reality can be read and interpreted. The investigation has a bibliographic and documentary character, based on cultural history, articulated with the aesthetic elements of literary studies and the educational field. In this way, we understand literature as a problematizing art that transcends the temporal line and reveals everyday forms of life in the most diverse social groups, including childhood within this context. The research results demonstrated that the Coraliniano text, through representations, constitutes a significant source for analyzing facts and events in the City of Goiás during the defined period (end of the 19th century and part of the 20th). We also highlight Cora Coralina's sing as another voice that problematized the history of diverse experiences: childhood, ways of educating them, youth and female action in the face of patriarchal commands and excesses.